2018
DOI: 10.21511/pmf.07(2).2018.01
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of informal SMEs’ potential in an African economy – theoretical and conceptual framework

Abstract: Informal Small and Medium Enterprises (SMEs) play a key role in their respective economies over the world particularly in the African continent. This paper reviews various theories on SMEs towards understanding the potential of the informal sector in the context of African countries. The paper uses a theoretical approach for the purpose of assessing the challenges that have affected the development of the informal SMEs sector over the years in both the developing and developed world. Economically developing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…In the Zimbabwean SME agro-processors context, research on the linkage between digital marketing capabilities and market performance is scarce. Previous research has dominantly focussed on agro-processors challenges (Mhazo et al, 2012), SME policy issues (Chigwenya & Mudzengerere, 2013), informal sector (Matsongoni & Mutambara, 2018), and government policies on SMEs (Bomani, 2016). Linking SME agro-processors' digital marketing capabilities to performance is important in the Zimbabwean context and other developing countries with similar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the Zimbabwean SME agro-processors context, research on the linkage between digital marketing capabilities and market performance is scarce. Previous research has dominantly focussed on agro-processors challenges (Mhazo et al, 2012), SME policy issues (Chigwenya & Mudzengerere, 2013), informal sector (Matsongoni & Mutambara, 2018), and government policies on SMEs (Bomani, 2016). Linking SME agro-processors' digital marketing capabilities to performance is important in the Zimbabwean context and other developing countries with similar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They must be strategic. Research has proved that the majority of informal businesses fail within a few years after start-up due to not being strategic [25]. This research has concluded that informal entrepreneurs operated businesses above 5 years have learned know how to sustain.…”
Section: Resultsmentioning
confidence: 96%
“…The study contributes to digital marketing literature by applying existing knowledge to a digital and developing country context. This is crucial to the Zimbabwean context because existing research (Matsongoni & Mutambara, 2018;Mapakame, 2017;Bomani, 2016;FinScope, 2012;Mhazo, et al, 2012;Zindiye, et al, 2012) mainly focus on SME financial issues, accounting practices, government policy, general challenges and constraints.…”
Section: Discussionmentioning
confidence: 99%